Removal of lignin from meranti wood sawdust for enhances enzymatic hydrolysis and production of sugar alcohol - Rusmawarni, Ramli (2012)
Nowadays, consumers, worldwide, are becoming increasingly aware of the relationship between food or food constituents and health. Sugar alcohol or polyols, which are being used as sucrose substitutes, are found in small quantities in nature, mainly in fruits and vegetables. The major aim of this research is to produce sugar alcohol from meranti wood sawdust using three important phases of the processes; pretreatment (pre-delignification, first treatment and second treatment), hydrolysis and fermentation. The objective of this research is to recover cellulose content and parallel with lignin degradation. Besides, enzymatic hydrolysis of cellulose recovery from pretreatment process to produce glucose with high yield also was being done. Fermentation of glucose production from cellulose to produce sugar alcohol is the major objective of this research. A series of preliminary studies were being performed prior to the investigation of the lignin degradation based on meranti wood sawdust to enhance enzymatic hydrolysis and also fermentation process to produce sugar alcohol. Furthermore, the characterization of meranti wood sawdust, glucose and sugar alcohol also respectively being discussed and that characterization was being obtained from Fourier Transform Infrared (FTIR), Ultraviolet Visible Spectroscopy (UV-VIS) and Scanning Electron Microscopic (SEM). After PAA treatment, the degree of delignification was increased by 77.5% from total of lignin (after alkaline) and the lignin content was decreased to 5.1%. This result indicated PAA was a very selective delignification agent and this chemical treatment will proceed with second stage of treatment using dilute sulfuric acid as an agent to remove hemicelluloses and lignin. Apparently, the optimal value of 86.0799% was obtained in the pretreatment stage. However, the optimal value of glucose production was 1028.35mg/L after RSM being applied.